Back Cover: In Situ Fabrication of Ag/Ag3PO4/Graphene Triple Heterostructure Visible‐Light Photocatalyst through Graphene‐Assisted Reduction Strategy (ChemCatChem 6/2013). Issue 6 (30th May 2013) - Jiang, Baojiang; Wang, Yanhui; Wang, Jian‐Qiang; Tian, Chungui; Li, Wenjun; Feng, Qingmao; Pan, Qingjiang; Fu, Honggang
<x xml:space="preserve">Abstract</x> Never to fade away The cover picture shows visible‐light photocatalysis by Ag/Ag3PO4/graphene triple heterostructure composites in the degradation of organic contaminants. In their Full Paper on p. 1359 ff., B. Jiang, H. Fu et al. describe the in situ fabrication of the Ag/Ag3PO4/graphene triple heterostructure through the redox reaction between Ag+ and graphene. This structure could improve the charge‐separation rate under visible light and the inhibition of the photocorrosion phenomenon of Ag3PO4 gives high structural stability. This facile method has promise for the fabrication of diverse graphene‐based heterostructure photocatalysts.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>